MACROECONOMIC INDICATORS AND HUMAN DEVELOPMENT INDEX IN TEN LOWEST MEDIUM IN INDONESIA: AN ISLAMIC PERSPECTIVE - Kadir, Rifadli D; Ismail, Juniaty (STIE Kusuma Negara, 2020)
The human development index is an important issue because many developing countries have succeeded in achieving high economic growth but failed to reduce the gap in human development. The phenomenon is happening right now, there is a significant difference between one region and another indicates that there has not been equitable development in Indonesia. According to the Indonesian HDI Ranking Data source, there are 10 provinces which are at the bottom of the HDI ranking. This study aims to examine the reasons why the 10 Provinces are at the bottom of the HDI ranking using panel data and the Fixed Effect Model (FEM) regression model. The results showed that the variable economic growth and poverty had no significant effect on Human Development represented by HDI, the GRDP variable per capita had a negative and significant effect on HDI and the minimum wage variable had a positive and significant effect on HDI.